2021
DOI: 10.21608/ejchem.2021.69572.3528
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of bioactive compounds extract from Saussurea costus against food spoilage microorganisms

Abstract: Saussurea costus had a wide range of antimicrobial activities which used as alternative for synthetic preservatives that threaten human health. This study aimed to identify the bioactive compounds in S. costus extract (SCE) and to evaluate its antimicrobial activity against some pathogenic microorganisms. HPLC and GC-MS were used to quantify the bioactive compounds in SCE. The results indicated that ethanol and ethyl acetate extracts had the highest levels of polyphenols followed by n-butanol, and then n-hexan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…They were found in many plant families, such as Acanthaceae, Amaranthaceae, and Costaceae, and can cause toxicity [35]. The results obtained agreed with the formerly obtained results [17,32], which found that the main components isolated from S. costus roots are sesquiterpene lactones such as costunolide and dehydrocostus lactone, which have antibacterial, antifungal, and cytotoxic effects.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…They were found in many plant families, such as Acanthaceae, Amaranthaceae, and Costaceae, and can cause toxicity [35]. The results obtained agreed with the formerly obtained results [17,32], which found that the main components isolated from S. costus roots are sesquiterpene lactones such as costunolide and dehydrocostus lactone, which have antibacterial, antifungal, and cytotoxic effects.…”
Section: Discussionsupporting
confidence: 86%
“…Using the "cup plate diffusion" method, the petroleum ether, chloroform, methanol, and water extracts of S. lappa (synonym for S. costus) were tested against Gram + and Gram − bacteria; the chloroform extract yielded the best results [31]. S. costus extracts, according to [32], can play a significant role in the defense action against human multi-resistant bacteria and can be used instead of antibiotics in the treatment specific diseases. The current effectiveness of S. costus phytochemicals in controlling several C. albicans and NAC species advocates their applicability for combating other serious emerging species like C. auris.…”
Section: Discussionmentioning
confidence: 99%
“…These bioactive compounds in fruits methanolic extract possess effective antifungal [ 37 ] and antimicrobial activity [ 38 ], including polysaccharides, which act as an osmoprotective mechanism of plants involved in immunity [ 39 ]; organic acids used as herbicides, utilized as a precursor for the synthesis of the antiviral drugs and antibacterial agents [ 40 , 41 ]; fatty acids which play an important role in fungal resistance [ 42 , 43 ]; and antioxidant components, which help the plant to protect itself against various types of oxidative damage [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Table : 1). Roots of this plant was cleaned, dried, and kept according to [11]. • Extraction of the Crude Alkaloid Compounds: Crude Alkaloid compounds were extracted according to [12].…”
Section: Plant Materialsmentioning
confidence: 99%